Ochratoxicosis in the Goat - Maryamma K I (Department of Pathology, College of Veterinary and Animal Sciences, 1983)
An experimental study was carried out to delineate the pathological effects of ochratoxin in goats. A comparative assessment of ochratoxin production by A. ochraceus and A. sulphureus on what and rice under static and shake cultures was also made. A. ochraceus was found to be a better toxin producing strain in both substrates under static and shake cultures systems and wheat was a better substrate than rice. Toxicity studies were conducted in Sannen – Malabari cross-bred goats of 1 to 3 months age. Purified ochratoxin produced in the laboratory was administered by oral, intra-peritoneal and intravenous routes. The different dose levels adopted were 2.5 mg/kg body weight, 1 mg/kg body weight and 0.5 mg/kg body weight. The synergistic effect of ochratoxin and aflatoxin in goats was studied by adminstering the crystalline toxins simultaneously (Makor Chemicals, Israel) by itraperitoneal route. The parameters of study were: clinical signs, haematological and biochemical alterations, pathological changes in urine, and macroscopic, microscopic and ultra-structural alterations in organs. Varying degree of clinocopathological changes were noticed in the test animals. The animals became weak and listless and in general there was reduction of total erythrocyte count, PCV, haemoglobin and lymphocyte count. Serum protein level was lowered while BUN and creatinine and blood coagulation time were high. There was rise in ALP, SGOT and SGPT in some of the test animals. The changes and degree of variation depended on the dose, total quantity and rate of administration of the toxin and duration of the experiment. More severe alterations were noticed when ochratoxin and aflatoxin were administered simultaneously. Important changes in the urine were lowering of pH, albuminurea and presence of epithelial cells and casts. Pathological changes varied in severity in different organs and were observed in the following descending order: kidney, liver, intestines, stomach, lymph nodes, spleen, thymus, genital organs, endocrines. In the kidneys, the order of intensity of pathological alterations was: proximal convoluted tubules, Henle’s loop, distal convoluted tubule, glomeruli, collecting tubules. Retrogressive changes of different degree and necrosis of the lining epithelial cells of tubules and endothelium and epithelium of glomeruli were the important lesions. Changes in glomeruli and Bowman’s capsule noticed in the higher dose group included shrinkage of glomeruli and presence of proteinaceous material in the capsular space. Eosinophilic granular casts and PAS positive bodies were present in the lumen of tubules. The necrobiotic renal changes were more intense when orchatoxin and aflatoxin were administered simultaneously. Hepatic lesions were mainly fatty infiltration, necrosis of hepatocytes and haemorrhage. The changes were most severe in combined toxicity. Mallory bodies and mild biliary hyperplasia were noticed in a few sections. Necrosis and subsequent depletion of lymphocytes wee the lesions in lymph nodes, spleen and thymus in some test animals. Degenerative changes were also noticed in testis, ovary, pituitary, adrenals and pancreas in experimental groups. In the combined toxicity group the pathological effect was more intense. At the ultra-structural level, the hepatcytes as well as the epithelial cells in the kidney showed severe changes. The cell organelles were either completely damaged or showed partial configurational alterations. Mitochondria showed changed in the density of matrix as well as disorientation and destruction of the limiting membranes and cristae. Cytolysosomes incorporating damaged cell organelles were abundant. Disaggregation of ribosomes and fragmentation of ER were noticed. In the glomerulus, there was destruction of the basement membrane and disruption of the regular arrangement of the foot processes of podocytes. In the cytoplasm of hepatocytes, Mallory bodies and lipid droplets were present. Varying degree of nuclear changes like clumping, condensation and disappearance of chromatin and fragmentation of nucleolus and nuclear membrane were observed. Changes occurred in the tight junctions of epithelial cells of bile ducts. Pathological alterations were more pronounced when ochratoxin was administered by the pwerenteral route. Oral administration of toxin also effected structural alterations which indicated that some fraction of ochratoxin escaped degradation in the rumen. From this study it became evident that aflatoxin potentiated the effect of ochratoxin. The structural damage to the cells might be due to the inhibition of oxidative enzymes which is reflected by the extensive ultra- structural alteration observed in the mitochondria and RER. Biochemical changes like high BUN and creatinine were evidently due to necrobiotic changes in the kidney. Interference in the synthesis of proteins due to damage of hepatic cells and escape of protein molecules due to alteration in the podocyte foot processes and basement membranes may account for the reduced serum protein levels. The nature of organellar destruction and configurational changes in the cells indicate the toxic potency of the mycotoxin on the biological system.